Role of macrophage CCAAT/enhancer binding protein delta in the pathogenesis of rheumatoid arthritis in collagen-induced arthritic mice. - Ling-Hua Chang; Huei-Sheng Huang; Po-Ting Wu; I-Ming Jou; Min-Hsiung Pan; Wen-Chang Chang; Dennis Ding Hwa Wang; Ju-Ming Wang (PLoS ONE, 2012)
BACKGROUND: The up-regulation of CCAAT/enhancer binding protein delta (CEBPD) has frequently been observed in macrophages in age-associated disorders, including rheumatoid arthritis (RA). However, the role of macrophage CEBPD in the pathogenesis of RA is unclear. METHODOLOGY AND PRINCIPAL FINDINGS: We found that the collagen-induced arthritis (CIA) score and the number of affected paws in Cebpd(-/-) mice were significantly decreased compared with the wild-type (WT) mice. The histological analysis revealed an attenuated CIA in Cebpd(-/-) mice, as shown by reduced pannus formation and greater integrity of joint architecture in affected paws of Cebpd(-/-) mice compared with WT mice. In addition, immunohistochemistry analysis revealed decreased pannus proliferation and angiogenesis in Cebpd(-/-) mice compared with WT mice. CEBPD activated in macrophages played a functional role in promoting the tube formation of endothelial cells and the migration and proliferation of synoviocytes. In vivo DNA binding assays and reporter assays showed that CEBPD up-regulated CCL20, CXCL1, IL23A and TNFAIP6 transcripts through direct binding to their promoter regions. CCL20, IL23A, CXCL1 and TNFAIP6 contributed to the migration and proliferation of synoviocytes, and the latter two proteins were involved in tube formation of endothelial cells. Finally, two anti-inflammatory chemicals, inotilone and rosmanol, reduced the expression of CEBPD and its downstream targets and mitigated the above phenomena. CONCLUSIONS AND SIGNIFICANCE: Collectively, our findings suggest that CEBPD and its downstream effectors could be biomarkers for the diagnosis of RA and potentially serve as therapeutic targets for RA therapy.